2017
DOI: 10.1111/1471-0528.14640
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of uterine fibroids: a systematic review

Abstract: Background Uterine fibroids (UFs) are the most common neoplasm affecting women that can cause significant morbidity and may adversely impact fertility.Objectives To examine UF epidemiology and to evaluate the relative strengths of putative risk factors.Search strategy MEDLINE and Embase were searched for studies published in English between January 1995 and April 2015.Selection criteria Publications reporting relevant data from registries and other observational studies with over 1000 patients and single-centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
526
8
27

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 726 publications
(652 citation statements)
references
References 107 publications
17
526
8
27
Order By: Relevance
“…The incidence is increasing continuously and surgical treatment is still the most common treatment strategy. However, that can affect patients’ physical and psychological health . Recent decades has witnessed the progression on discovering the pathogenic factors that are related to leiomyoma including the environmental, genetics, hormonal and growth factors as well as some hormone‐related factors .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is increasing continuously and surgical treatment is still the most common treatment strategy. However, that can affect patients’ physical and psychological health . Recent decades has witnessed the progression on discovering the pathogenic factors that are related to leiomyoma including the environmental, genetics, hormonal and growth factors as well as some hormone‐related factors .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of fibroids has been historically underestimated by epidemiologic studies which focused mainly on symptomatic women, leaving behind a large population of asymptomatic women and women who underreport their symptoms . The prevalence of fibroids varies among different studies and countries (4.5%–68.6%) based on the type of investigation, method of diagnosis, and racial/ethnic demographics of the population studied . Recent research from the United States has shown that fibroids are detected by ultrasound in more than 80% of women of African ancestry and nearly 70% of white women by the age of 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is a greater occurrence of uterine and tubal anomalies with greater maternal ages. The uterine pathologies include endometrial polyps and uterine fibroids whose occurrence is greater with advancing maternal age [14]. Fibroids, especially those with a sub mucosal or intramural component are associated with low fertility.…”
Section: Discussionmentioning
confidence: 99%